Muscle loss 6 months after surgery predicts poor survival of patients with non-metastatic colorectal cancer - Zhang, Liang; Guan, Junjie; Ding, Chao; Feng, Min; Gong, Longbo; Guan, Wenxian (Frontiers in Nutrition, 2022)
Background: Sarcopenia is a common characteristic of cancer-related malnutrition and a predictor of poorer prognosis in oncological patients. This study evaluated the association between altered body composition six months after surgery and the prognosis in patients with nonmetastatic colorectal cancer. Methods: A total of 314 patients who underwent elective curative surgery were enrolled in the study. The third lumbar CT images on preoperative and 6-month postoperative were collected to calculate the skeletal muscle index (SMI), visceral adiposity index (VATI) and subcutaneous adiposity index (SATI). Sarcopenia was defined by the cut-off values reported in the literature, and risk factors affecting overall survival (OS) and disease-free survival (DFS) in CRC were analyzed using Cox regression models. Results: Eighty-two of 314 patients (26.1%) with CRC were diagnosed with sarcopenia before surgery, the preoperative sarcopenia was not significantly associated with the prognosis of CRC patients. Patients with SMI loss are more likely to develop incisional hernia (18.40% vs 2.6%, p<0.001) after surgery than the patients with non-SMI loss. In multivariate analysis, 6-month SMI loss >10% after surgery was independently associated with poorer OS [hazard ratio (HR)= 3.74; 95% confidence interval (CI) 1.96 to 7.12; P<0.001] and DFS (HR=3.33; 95% CI, 1.71 to 6.47; P<0.001). SMI changes were moderately correlated with changes in body mass index (BMI) (R=0.47, P<0.001). Conclusions: 6-month muscle loss after surgery may affect overall and disease-free survival and was an independent predictor of prognosis in patients with CRC. Muscle loss after surgery may be a potential risk factor for incisional hernia.